Midline fasciotomy for severe acute pancreatitis with abdominal compartment syndrome: Case report. (July 2022) - Kawasaki, Yuki; Kamidani, Ryo; Okada, Hideshi; Nakashima, Yusuke; Yamaji, Fuminori; Fukuta, Tetsuya; Yoshida, Takahiro; Yoshida, Shozo; Ogura, Shinji
Abstract: Introduction and importance: The abdominal compartment syndrome (ACS) is defined as new-onset organ failure induced by sustained elevated intra-abdominal pressure (IAP). Surgical decompression to decrease IAP may be performed in addition to supportive therapy. Case presentation: A 42-year-old woman with a history of type 2 diabetes, dyslipidemia, alcohol disorder (130 g of daily alcohol intake), and schizophrenia presented to the emergency department with worsening abdominal pain and anorexia for 2 days. On arrival, her Glasgow Coma Scale score was 14 (E3V5M6). Physical examination revealed tachypnea with a respiratory rate of 26 breaths/min; other vital signs were stable. She was diagnosed with severe acute pancreatitis and required massive transfusions to stabilize her hemodynamic status from the time of admission to the intensive care unit (ICU). Acute blood purification was initiated. Bilateral pleural effusions increased from the second day, and despite the evacuation of the intraluminal contents, muscle relaxation was initiated because her IAP had increased to 52 mmHg and remained the same. Therefore, midline fasciotomy was performed instead of a midline incision through the linea alba on day 4, and the patient was managed with negative pressure wound therapy thereafter. Blood purification was completed on day 15, extubation was performed on day 17, and the patient was discharged from the ICU on day 29. Clinical discussion and conclusion: Midline fasciotomy can have a decompressive effect in patients with primary ACS. This technique may be an alternative to decompressive laparotomy because of its less invasive nature. Highlights: A 42-year-old woman was diagnosed with severe acute pancreatitis. Muscle relaxation was initiated because of elevated intra-abdominal pressure. Midline fasciotomy was successfully performed instead of a midline incision. Midline fasciotomy may be an alternative to decompressive laparotomy.